Serum pituitary gonadotropins during the menstrual cycle, measured by radioimmunoassay - Llerena, Luis (2015)
Radioimmunoassay techniques being used, have determined the levels of serum LH and FSH through the menstrual cycle, 15 cycles of 12 normal women of reproductive age (23-35 years). Eleven women had a rise in LH levels at mid-cycle (days 12-21). Six of these women also had significantly elevated levels of FSH, LH coincide with, and one woman had an elevation of FSH a day after the rise in LH. The highest level of LH achieved ranged from 33.5 to 160 mIU / ml. IRP-HMG-2 (mean ± is 90.8 ± 10.9) and FSH fluctuated between 26.5 and 44.0 mIU / ml. (Average is 31.6 ± ± 2.5). The levels of LH and FSH during the follicular phase (LH and FSH 19.5 16.3 -1 3.2 ± 2.1) were higher than in the luteal phase (LH FSH 9.5 ± 3.5 7.7 ± 3.1). FSH / LH ratio was lower during the ovulatory phase (0.35) during the first (0.83) and last days (0.81) of the cycle.